Does political instability lead to higher and more volatile inflation? A panel data analysis - Veiga, Francisco José (2003)
Economists generally accept the proposition that high and volatile inflation rates generate inefficiencies that reduce society’s welfare. Furthermore, studies have shown that inflation is harmful to economic growth. However, determining the causes of the worldwide diversity of inflationary experiences is an important challenge not yet satisfactorily confronted by the profession. Based on a broad dataset covering over 100 countries for the period 1975-1997 and using dynamic and static panel data econometric techniques, this paper shows that a higher degree of political instability is associated with both higher inflation levels and volatility. Not only does this paper advance the political economy literature establishing a relationship between inflation moments and political instability, but it also has important policy implications regarding the optimal design of inflation stabilization programs and of the institutions favorable to price stability.